Figure 8 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 8 - SEM images of male Caurinus tlagu (UAM:Ento:204239), scale bars = 100 µm A dorsal view showing wings B evertedgenitalia showing paired gonostyles, oblique lateral view.